Microarray analysis of canine osteosarcoma cells exposed to Colombian propolis - Dolly Patricia Pardo-Mora; Oscar Julián Murillo; Mauricio Rey Buitrago; Anny Rodríguez; Jaime Fabian Cruz Uribe; José Maurício Sforcin; Orlando Torres García (Elsevier, 2022)
Background: Propolis is a bee product exhibiting a cytotoxic activity against tumor cells. This study aimed at investigating the gene expression profile of canine osteosarcoma cells exposed to Colombian propolis by microarray analysis, in an attempt to identify differentially expressed genes and the pathways involved in propolis cytotoxic action. Methods: The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase assays were used to assess the viability and the half-maximal inhibitory concentration for OSCA-8 cells and fibroblasts after incubation with propolis samples, its solvent (70% ethanol) or doxorubicin (positive control). The gene expression profile was determined by the Canine Gene 1.0 ST Array (Affymetrix) and the microarray data was validated by real time PCR. Enrichment and annotation analysis were applied for the differentially expressed genes. Results: Propolis reduced cell viability and exerted a cytotoxic effect on OSCA-8 cells, exhibiting a selective effect in relation to non-tumor cells. The microarray analysis showed changes in more than 253 genes involved in intracellular pathways related to the inflammatory response, growth factor activity and chemotaxis, which are associated with cancer development. Propolis exerted doxorubicin-like changes in gene expression. Conclusion: Propolis and Dox exerted a similar action, altering some pathways and indicating possible mechanisms of action involved in the cytotoxic effect on OSCA-8 cells.